POSISI PEREMPUAN PADA TEKS WACANA SASTRA: PEMBACAAN ANALISIS KRITIS - Besse Herdiana (TELAGA BAHASA, 2020)
This study aims to describe the position of women in the text of literary discourse. This research is a qualitative description. The data source in this study is the Ronggeng Dukuh Paruk novel by Ahmad Tohari and Tarian Bumi by Oka Rusmini. Data collection is done by observation, literature review, and recording techniques. The results showed that the choice of words used by male authors to describe the position of female actors in the Ronggeng Dukuh Paruk novel tended to marginalize women with bad (negative) portrayals and male actors were portrayed as ordinary. The event is fulfilled with the choice of refining words. While female authors in the Tarian Bumi novel provide identification to women with names that are inherent and described as they are and male actors are portrayed poorly. The event is described by the word dysphemism.